Administration of caseinomacropeptide-enriched extract to mice enhances the calcium content of femur in a low-calcium diet. (May 2015) - Burns, P.; Binetti, A.; Torti, P.; Kulozik, U.; Forzani, L.; Renzulli, P.; Vinderola, G.; Reinheimer, J.
Abstract: Caseinomacropeptide (CMP) is the 64 C-terminal amino acid residue of κ-casein, formed by chymosin cleavage during cheese manufacture. This study examined the effects of oral administration of a CMP-enriched extract (CMPEE), obtained from a local dairy plant, on the Ca content of mouse femurs. Animals received low (0.1%, w/v), normal (0.5%, w/v) or high (1.2%, w/v) Ca diet for 3 or 8 weeks and CMPEE diluted (1:10) in their drinking water. No significant differences in Ca content were observed in faeces, kidney, urine or blood serum compared with control animals. The oral administration of CMP to mice significantly enhanced the Ca content in femur under a low-Ca diet model, especially during the period of full body development (3 weeks), in which case a significant 12% Ca increase was observed. These findings pave the way for further studies aimed at supplementing infant food with industrially-obtained CMP-enriched extract for enhanced bone health.